1997
DOI: 10.1006/jmbi.1997.1252
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for the in vitro evolution of protein function: enzyme evolution by random recombination of improved sequences 1 1Edited by J. Wells

Abstract: Sets of genes improved by directed evolution can be recombined in vitro to produce further improvements in protein function. Recombination is particularly useful when improved sequences are available; costs of generating such sequences, however, must be weighed against the costs of further evolution by sequential random mutagenesis. Four genes encoding para-nitrobenzyl (pNB) esterase variants exhibiting enhanced activity were recombined in two cycles of high-®delity DNA shuf¯ing and screening. Genes encoding e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
1
3

Year Published

1998
1998
2003
2003

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(74 citation statements)
references
References 14 publications
2
67
1
3
Order By: Relevance
“…Combinatorial and directed-evolution methods have proven to be promising techniques for designing proteins of novel structure and function (27,28). These methods systematically generate a large number of sequences and it is imperative to be able to detect successful de novo designs from a large background of unfolded polypeptides.…”
Section: Resultsmentioning
confidence: 99%
“…Combinatorial and directed-evolution methods have proven to be promising techniques for designing proteins of novel structure and function (27,28). These methods systematically generate a large number of sequences and it is imperative to be able to detect successful de novo designs from a large background of unfolded polypeptides.…”
Section: Resultsmentioning
confidence: 99%
“…Although simple DNA base substitutions are well suited for the generation, diversification, and optimization of local protein space (Maeshiro and Kimura 1998), a hierarchy of natural mutational events is required for the rapid generation of protein diversity. Experimental evolution (Moore et al 1997;Zhang et al 1997;Crameri et al 1998) and computer simulation experiments (Bogarad and Deem 1999) showed that sequence shuffling has the potential to improve protein function significantly better than does point mutation alone. Because they are uniquely competent to reshuffle DNA sequences, TEs and viruses are important generators of the more complex types of mutations in the mutational hierarchy.…”
Section: Broad-spectrum Mutator Mechanismsmentioning
confidence: 99%
“…20 For N sequences with M total mutations, the probability of generating the sequence containing all of the mutations (the rarest sequence) by random recombination is 1/N M . This becomes small very quickly when multiple sequences (or many mutations) are recombined.…”
Section: "Sexual" Evolution By Gene Recombinationmentioning
confidence: 99%